Pre-weaning performances and mortality rate of calf Bali cattle maintained in the community with smallholder and intensive systems. (March 2019) - Baco, Sudirman; Malaka, Ratmawati; Hatta, Muhammad; Zulkharnaim,
Abstract: Bali cattle are native cattle of Indonesia, which is widely maintained by farmers and is a source of income for livestock farmers in South Sulawesi and even as a source of national meat food from beef cattle. Therefore, this livestock is the main commodities of South Sulawesi in the field of animal husbandry. Based on this, the Hasanuddin University Research Master Plan (RIP), Bali cattle is the main priority in the development of superior commodities in the field of animal husbandry. The problem is that the calf mortality rate is still very high (30-50%), the performance of Bali cattle breeds is still low. It can be seen that it is very difficult to get female cows with shoulder height exceeding 104 cm. The high rate of calf mortality and the low level of productivity of livestock may be due to farmers not paying attention to the management factors and cows breeding used. Therefore, it is necessary to conduct comprehensive and sustainable development research, how to reduce calf mortality rates and improve the performance of Bali cattle breeding sustainability through improved management in the calf phase. The aim of the study was to determine the level of performance and mortality rates of calves of Bali cattle that were maintained traditionally in the community and intensive systems. To achieve this goal, the research method was designed to improve feed and management in the calf phase continuously. Research parameters were calf mortality rate, calf growth (calf body weight) and body dimensions before weaning. Analysis of the data used was descriptive analysis and t-independent test. The results of the study show the following: 1) the calf mortality rate before weaning was high (maintained in the community 49.5% and intensive 9%), 2) the calf growth before weaning differs significantly between the calf that was maintained with a system of maintenance the community without the additional feed (existing management) and intensive feeding, 3) the changes in rates of growth and parts of the body dimensions of livestock that were given a quality feed and improved management in the calf phase vary between one part and another.